MOTIVATION POLICY FOR TEACHERS IN VIETNAM’S UNIVERSITIES - Nguyen Kim Dung; Pham Thu Trang (IJRDO - Journal of Social Science and Humanities Research, 2019)
Recently, the implementation of policies to create motivation to develop teachers at university has achieved good results, gradually creating a favorable legal environment for organizing and implementing development goals both in quantity, quality and structure. However, in addition to the achieved aspects, the implementation of policies with lecturers at universities is still limited, inadequate, directly affecting the implementation of policy objectives. The correct assessment of the current status of policy implementation for lecturers is an important factor in order to provide effective solutions and propose solutions to improve policy contents.